Efeito da reidratação nos aspectos ecofisiológicos da Copaifera langsdorffii Desf - Rodrigues, Angélica Lino [UNESP] (2013)
The extreme environmental conditions due to the seasonality of the Cerrado promote physiological changes in plants in response to stress conditions. Stress is the effect caused from one or more external factors leading to deficiency or decreased metabolism and / or development of the plant. Many woody species exhibit morphological, physiological and biochemical mechanisms to overcome potential inadequate supply of water, such as changes in the pattern of growth, development of vegetative organs, changes in stomatal conductance, adjust of the osmotic potential from tissue and production of substances of secondary metabolism. The present study aims to evaluate the ecophysiological aspects of Copaifera langsdorffii Desf. in Cerrado and controlled system in order to analyze the adjustments of this species with respect to water deficits characteristic of the environment to which the species is found. C. langsdorffii presented similar adjustments in water relations in both environments studied, with slow recovery of stomatal conductance after rehydration and immediate response of the relative water content. The water potential leaf in predawn in field conditions indicated no statistical difference between the rainy and dry seasons, confirmed the ability of tissue rehydration night regardless of season and water condition. In field conditions, with the accumulation of precipitation, there was an increase of stomatal conductance, even with lower water potential in midday. The photochemical efficiency evaluated through the parameters of chlorophyll fluorescence shows that the quantum yield is affected by the drought, however this process can be restored with the availability of water. Thus, the species in this study has the ability to resume the photochemical performance taking the same values before to stress. Increased enzyme activity in the field after the stress period and decreased in favorable water conditions. The species C. langsdorffii ...